Pathology of bone epiphyses and frequency of various damage degree cases in patients with rheumatoid arthritis complicated by knee joint frontal deformities - V. V. Hryhorovskyi; Ye. M. Avtomieienko (Zaporozhye State Medical University, 2020)
Aim: based on several semi-quantitative morphometric indices, which represent pathological changes in femoral and tibial condyles, to determine pathological changes occurrence frequencies of damaged knee joints, complicated by frontal deformations. Materials and methods. Resected femoral and tibial condyles, obtained during knee replacement in 38 patients with rheumatoid arthritis and deformations of knee joints in frontal plane, served as material of current study. The following research methods were used: clinical examination, histological with semi-quantitative morphometric indices determination; statistical with determination of mean parameters, frequency of occurrence of cases with different gradations of indicators expression and their differences. Results. Groups of rheumatoid arthritis patients with lesions of knee joints complicated by deformities in frontal plane of different forms (valgus - varus), had significant differences by several clinical and clinical-visual indices. Pathological changes of epiphyses which are reflected by such morphometric parameters as "pannus structure and inflammation", "inflammatory activity in subchondral spongiosa" and "stage of dystrophic-destructive changes of the joint surface" with different frequency and severity occur in the tissues of all rheumatoid arthritis patients with knee injuries, complicated by frontal deformations. In condyles from bones of one type, that form knee joint, compared in varus and valgus deformities, occurrence frequency of varying severity cases of separate morphometric indices varies in condyles according to different degree of compression. In condyles from bones of one type, which form knee joint, compared in different bones (femur and tibia) in cases of valgus deformity there was higher occurrence frequency of cases with more expressed indicator of "pannus structure and inflammation" in tibial condyles, in cases of varus deformity - in femoral condyles (independent of degree of compression). Conclusions. Results of study showed that degree of both clinical and morphometric indices of tibia and femur condyles condition in patients with rheumatoid arthritis and knee joint frontal deformities has no constant, unambiguous tendencies, and occurrence frequencies of cases with high and low degrees vary in wide limits.